1995
DOI: 10.1109/66.382275
|View full text |Cite
|
Sign up to set email alerts
|

Quality and reliability impact of defect data analysis

Abstract: In the last decade we have seen a shift towards a broader application of information on IC manufacturing defects.Here an overview will be given of the methods used to gather data on the defects with a focus on local defects in the interconnection layers. Next this information is applied to determine a model describing the geometrical aspects of such defects. This model is used to come to the definition of hard faults and soft faults and to derive a relationship between the relative number of occurrence for eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For a regular array of tracks of width and separation the sensitivity to hard faults , for defects with diameter , is given by for for for (1) The sensitivity to both hard and soft (H&S) faults [2] is given by for for for (2) Taking a of , as a conservative definition of the defect size that can cause a soft fault, and gives the sensitivity function shown in Fig. 2.…”
Section: Circuit Faultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a regular array of tracks of width and separation the sensitivity to hard faults , for defects with diameter , is given by for for for (1) The sensitivity to both hard and soft (H&S) faults [2] is given by for for for (2) Taking a of , as a conservative definition of the defect size that can cause a soft fault, and gives the sensitivity function shown in Fig. 2.…”
Section: Circuit Faultsmentioning
confidence: 99%
“…This deterioration is related to both the thickness of the remaining dielectric and on the level of electrical activity at the affected nodes. It has been suggested that a minimum safe distance is half of the minimum track separation [2].…”
Section: Circuit Faultsmentioning
confidence: 99%
See 3 more Smart Citations